Biosorption of reactive dye Remazol Ultra Red RGB by metabolically active kefir biomass - Erdogdular, Ali Osman; Apar, Dilek Kilic (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2021)
In the present study biosorptive removal of Remazol Ultra Red RGB textile dye from aqueous solutions with living kefir biomass was investigated. The experiments were carried out at batch operation mode under different process conditions such as initial pH (2-2.5-3-3.5-4 -5- 6-7-8), temperature (18-25-32-39.), shaking rate (0-140-300 rpm) and initial dye concentration (50-75-100-200-400 mg/L) to optimize and model the biosorption process. 93% dye removal was attained in 180 min processing time by using 2.4 g/L kefir biomass for 100 mg/L initial dye concentration at pH 2 and 25.. The maximum adsorption capacity for kefir biomass was obtained as 118 mg/g at 400 mg/L dye concentration. Successively performed biosorption experiments showed that the kefir biomass is reusable. As a result of the modelling studies performed the biosorption kinetics and the equilibrium by kefir biomass were best described respectively with the Pseudo first order and the Temkin models.
Keywords: Remazol Red RGB; kefir biomass; biosorption; kinetics; isotherm; RESPONSE-SURFACE METHODOLOGY; TEXTILE EFFLUENT; DECOLORIZATION; WASTE; DEGRADATION; REMOVAL; CULTURE; YEAST; OPTIMIZATION; EQUILIBRIUM; Engineering